Tensegriture: Integrating Tensile Integrity into Furniture to Reduce Earthquake Damage (American Journal of Innovation in Science and Engineering, 2023)
Few furniture designs are built around the concept of withstanding earthquakes. This capstone project aims to integrate tensegrity into furniture to replicate the earthquake safety measures used on larger scales with seismic isolation and withstand earthquakes better than traditional furniture. The researchers tested the product at the Philippine Institute of Volcanology and Seismology (PHIVOLCS), located at Diliman, Quezon City. The researchers made use of the institute’s earthquake simulator to have the earthquake intensities scaled accurately. They made use of true experimental research design, which gave them access to the scientific method in making the designs for the furniture. The researchers conducted the experiment in four phases, denoted as the research phase, the design phase, the experiment phase, and the evaluation phase. The results showed that the calculated t-value of 35.317 is greater than the critical t-value of 2.56. This meant that tensegrity-integrated furniture is significantly more earthquake-resistant than traditional household furniture. Measures such as adding weights to the structure’s base increase further increase its stability. Tensile integrity integrated into furniture is a modern take on earthquake safety measures, similar to existing ones like seismic isolation. And with the proper setup and more improvements, its earthquake resistance factor can save lives.